Спеціальний слідчий експеримент як форма контролю за вчиненням злочину - Багрій, Микола Васильович; Багрий, Николай Васильевич; Bagrij, Nikolaj (Одеса : Юрид. л-ра, 2014)
In the article were analyzed concepts, peculiar features, reasons and processual order of conducting a special investigation experiment as a form of crime commission control. Also there were offered the most efficient ways of its usage in the course of prejudicial inquiry.
Багрій М. В. Спеціальний слідчий експеримент як форма контролю за вчиненням злочину / М. В. Багрій // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 389-391.
Keywords: спеціальний слідчий експеримент; оперативна провокація; оперативно-розшуковий захід; негласна слідча (розшукова) дія; контроль за вчиненням злочину; специальный следственный эксперимент; оперативная провокация; оперативно-розыскное мероприятие; негласное следственное (розыскное) действие; контроль за совершением преступления; special investigation act; operative provocation; operative-investigative action; secret investigative (detective) act; crime commission control